Aegokeras gazipashensis (Apiaceae), a new species from South Anatolia, Turkey - Duran, Ahmet; Samigullin, Tahir; Lyskov, Dmitry (Phytotaxa, 2023)
A new species, Aegokeras gazipashensis (Apiaceae), is described from South Anatolia, Turkey. It grows in mountain steppe formation of the Taurus Mountains in the district of Gazipaşa (Antalya province). The taxonomic affinities of the new species were determined by analyzing morphological data and a molecular phylogenetic study of nrITS. Aegokeras gazipashensis is morphologically similar to A. caespitosa but it differs mainly with growing habitat, non-caespitose habit, remains of old leaf bases, morphology of roots, leaves, and leaflets, presence of petiole, and stylopodium rim features. The anatomical structure of the fruit is given. The diagnostic morphological characters of A. gazipashensis are discussed. In addition, the geographical distribution of the new species and the morphologically related A. caespitosa species is mapped. In this study, an identification key with a description of the new species is provided along with statements about the habitat, ecology, phenology, and conservation status of the new species.